2013
DOI: 10.1007/s00134-013-2902-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of troponins in sepsis: a meta-analysis

Abstract: Elevated troponin identifies a subset of patients with sepsis at higher risk of death. Further studies are needed to define the precise role of troponins and their optimal cut-offs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
2
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 35 publications
1
99
2
11
Order By: Relevance
“…The timing of troponin measurement, troponin assay used (ie, TnT versus TnI), and hemodynamic stability at the time of troponin measurement differ substantially in prior studies 2, 7, 8. The majority of prior studies have examined short‐term mortality, while this study included assessment of 1‐year death rate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The timing of troponin measurement, troponin assay used (ie, TnT versus TnI), and hemodynamic stability at the time of troponin measurement differ substantially in prior studies 2, 7, 8. The majority of prior studies have examined short‐term mortality, while this study included assessment of 1‐year death rate.…”
Section: Discussionmentioning
confidence: 99%
“…A prior meta‐analysis of observational studies demonstrated increased all‐cause mortality in patients with elevated troponin (relative risk 1.9, 95% CI, 1.6–2.2). However, only 3 studies used TnT values 2. By contrast, other investigators have failed to validate troponin as an independent predictor of mortality in addition to severity of illness scores 9, 27, 28, 29…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations